Nutritional Profile of Kanikkar Women in Amboori Area - Felsy Thomas (Department of Home Science, College of Agriculture, 1989)
A study to assess the nutritional profile of Kanikkar women in Amboori area was conducted through ecological, socio-economic and food consumption survey, anthropometric, clinical and biochemical assessment and through time and motion studies.